Annual reports on NMR spectroscopy. (Annual reports on NMR spectroscopy, 2003)
Nuclear magnetic resonance (NMR) is an analytical tool used by chemists and physicians to study the structure and dynamics of molecules. In recent years, no other technique has grown to such importance as NMR spectroscopy. It is used in all branches of science where precise structural determination is required and where the nature of interactions and reactions in solution is being studied. Annual Reports on NMR has established itself as a premier means for the specialist and nonspecialist alike to become familiar with new techniques and applications of NMR spectroscopy. - Includes comprehensive review articles on NMR Spectroscopy - NMR is used in all branches of science - No other technique has grown to such importance as NMR Spectroscopy in recent years.